2017
DOI: 10.1016/j.intmar.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Product Placement in Video Games: The Effect of Brand Familiarity and Repetition on Consumers’ Memory

Abstract: Product placement in video games is gaining momentum as a means to target audiences in an indirect and engaging way. This study uses a 2 (high repetition vs low repetition) × 2 (high brand familiarity vs low brand familiarity) factorial design to test the effects of repetition and brand familiarity on consumers’ memory for brands placed in video games. Results suggest that consumers recall familiar brands placed in the video game better than unfamiliar ones. Familiar brands also performed better in a brand rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 66 publications
3
60
2
6
Order By: Relevance
“…And although well-known brands took part in the research, the fact that the players remembered them confirms the impact of product placement on brand recog-nition. This hypothesis is supported by literature (Marti- Parreno et al, 2017;Mau et al, 2008). The results showed that most respondents saw the product placement of all brands advertised in Final Fantasy XV and FIFA 19 games.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…And although well-known brands took part in the research, the fact that the players remembered them confirms the impact of product placement on brand recog-nition. This hypothesis is supported by literature (Marti- Parreno et al, 2017;Mau et al, 2008). The results showed that most respondents saw the product placement of all brands advertised in Final Fantasy XV and FIFA 19 games.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, new generations of consumers are harder to manipulate as nowadays they understand better how advertising works, and they don't accept the traditional marketing (Parreno, 2015). Even when gamers perceive the hidden advertising, they would prefer such approach to explicit advertising (Marti- Parreno et al, 2017). In this sense, traditional advertising can is turning obsolete.…”
Section: Introductionmentioning
confidence: 99%
“…Our French‐speaking students were more familiar with the BN brand than our Dutch‐speaking participants. Because research shows that brand familiarity affects advertising effectiveness within non‐adult target groups (Martí‐Parreño, Bermejo‐Berros, & Aldás‐Manzano, ; Phelps & Hoy, ), this was an additional reason to run separate analyses for both language groups.…”
Section: Resultsmentioning
confidence: 99%
“…Placement refers to product placement including where the product is sold, how efficiently it can be delivered to the consumer, and product or service accessibility (Martí-Parreño et al, 2017). Marketers need to ensure that the products and services are as easy to find as possible.…”
Section: Managing the 5 Psmentioning
confidence: 99%